The Individual Coaching Improves Spiritually Muslim Patients Hospitalized - Hamdan Hariawan; Oedojo Soedirham; Abu Bakar (Jurnal Ners, 2019)
Background: Inpatients who are attached in intravenous devices tend to experience physical discomfort. This condition can lead to the decrease in performing Salat as a Muslim prayer. The purpose of this study was to determine the effect of individual coaching on knowledge, attitude, and practice of Salat among Muslim inpatient. This study used quasi-experimental design.Mehods: The samples were 36 Muslim inpatients. The data were collected by self-constructed questionnaire and analyzed by using Independent t-test and Mann Whitney test with α ≤ 0.05.Results: Before giving intervention, the means of pretest score in both groups were 14.33+2.17 and 14.39+2.28 for knowledge, 26.17+2.31 and 26.50+3.17 for attitude, and 10.00+2.91 and 10.50+3.45 for practice. There was no significant difference scores of knowledge (p=0.941), attitude (p=0.924), and practice (p=0.635) between two groups before giving intervention. However, after giving intervention, these scores have changed to 19.00+1.72 and 14.89+2.29 for knowledge, 26.97+2.25 and 26.61+2.81 for attitude, 15.33+3.80 and 10.50+3.45 for practice and there was higher significance scores of knowledge (p=0.000), attitude (p=0.003), and practice (p=0.000) after giving intervention.Conclusions: Coaching is the suitable method to increase Muslim inpatients knowledge, attitude, and ability to practice Salat. This study recommends the nurse to do coaching as a nursing intervention in helping patient to perform Salat